About scientific researches of the image of Aldar Kose. (Eurasian Journal of Philology Science and Education, 2015)
This article deals with the image of Aldar Kose, one of the most famous mythological images of Kazakh folklore. From ancient times the image of Aldar Kose is the symbol of truth and ambition, humor and satire. Storiesabout him spiritually enrich people by their deep philosophical and didactic content. The author provides an overview of basic researches of Aldar’s image in the Kazakh science and expresses his point of view on this issue. Besides, the author makes the analysis of some well- known stories about Aldar Kose and evaluates the system of artistic means. The place and the role of Aldar Kose’s image not only in Kazakh, but also in the whole Turkic literature are defined in this article. Image of Aldar Kose is described as a really - lived man and as a collective satirical image of folklore.
Keywords: Aldar Kose; Kazakh folklore; Uzbek literature; Turkish literature; collective image; satire; humor; cheater; trickster